Size Distributions of Water-Soluble Inorganic Ions in Atmospheric Aerosols During the Meiyu Period in the Yangtze River Delta, China - Wu, Zhaoye; Liu, Duanyang; Zhao, Tianliang; Su, Yan; Zhou, Bin (Frontiers in Environmental Science, 2021)
In order to investigate the chemical composition distributions and pollution characteristics of Total water-soluble inorganic ions (TWSII) in the rain period (Meiyu) in the East Asian summer monsoon season, including the impact of Meiyu on air pollution in the Yangtze River Delta, East China, the gaseous pollutant concentrations, the 9 sizes segregated particles, and water-soluble inorganic ions of aerosols were measured on the north shore of Taihu Lake from June 4 to July 5, 2016. Results show that the values of ρ (TWSII) for PM1.1, PM1.1–2.1, and PM2.1–10 before the Meiyu onset are generally greater than those during the Meiyu period. The mass concentrations for anions, cations, and total ions at different particle-size sections all exhibit bimodal distributions before and after the Meiyu onset. The mass concentration peaks at a particle size of 1.1–2.1 μm for fine particles, while at 5.8–9.0 μm (before the Meiyu onset) and 9.0–10.0 μm (during the Meiyu period) for coarse particles, respectively. The mass concentrations of SO42− at different particle-size sections show a bimodal distribution before the Meiyu onset and a multi-modal distribution during the Meiyu period. The mass concentrations of NO3− at different particle-size sections show a bimodal distribution before the Meiyu onset and a unimodal distribution during the Meiyu period. The mass concentrations of NH4+ at different particle-size sections present a bimodal distribution before and after the Meiyu onset, with the particle-size for peak concentrations distributing in 1.1–2.1 μm and 5.8–9.0 μm before the Meiyu onset, and 9.0–10.0 μm during the Meiyu period. The mean value of NOR is higher before the Meiyu onset than after, indicating that the secondary conversion of NO2 before the Meiyu onset is enhanced. The SOR values are greater than NOR values, but the concentrations of NO2 in the same period during the Meiyu period are higher than those of SO2, which indicates that the secondary conversion of SO2 during the Meiyu period on the north bank of Taihu Lake is stronger than that of NO2.